Address Forms and Vocatives-Diminutives in Emily Brontë's Wuthering Heights - Kurniawati, Veronika Esther Diah; Sunarto, Emanuel (Journal Corner of Education, Linguistics, and Literature, 2025)
This present study is devoted to exploring the use of address forms and vocatives-diminutives in Wuthering Heights by Emily Brontë, with a focus on the way the use of language portrays the dynamic between the main characters and their emotions as well as their interpersonal relationships. With the help of a framework introduced by Klaus P. Schneider (2003) that captures diminutives as pragmatic speech act modifiers, the aim of the study is to identify specific types of vocative-diminutives and how they are used, with particular attention paid to Heathcliff, Catherine Earnshaw, and Edgar Linton's utterances. Through the use of a qualitative analysis method and library research, this study examines the chosen chapters of the novel by looking closely at the text and categorizing them according to their uses of diminutives in vocative, synthetic, and analytic forms. According to the results of the study, 27 diminutive forms are identified, and the most prevalent use of diminutives is the use of vocative full names, with seven instances. Following this, analytic vocative-diminutives are present six times, and synthetic vocative-diminutives could be found five times. In the meantime, vocative first names, vocative kinship terms, and vocative titles are all present twice, respectively. In addition, diminutive first names occur twice as well, whereas diminutive full names do not occur nearly as frequently, with only one instance.